Postglacial Vegetation, Climate History and Land-Sea Interaction at Island Lake, Baie des Chaleurs, New Brunswick, as Documented by Palynological Analysis - Mott, Robert; Jetté, Hélène; Guiot, Joël; Cloutier, André (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis study demonstrates that lakes located near the coast, close to large bodies of water, can document sea-level fluctuations and the subtle sea-land interaction that governs coastal areas. At Island Lake, located close to the head of Baie des Chaleurs, northern New Brunswick, the postglacial marine transgression corresponds with a reversal from a cold and dry herb and shrub tundra environment to open pioneer forest that was warmer and wetter. Successive incursions of poplar/aspen and spruce were succeeded by boreal forest dominated by spruce, alder and birch. A forest dominated by alder and fir, indicators of wetter and even colder local conditions followed. Paleoclimatic reconstruction inferred from pollen stratigraphy indicates that an early warming period culminating ca. 9450 BP, was followed by a period when temperatures remained cool. At the same time, the annual precipitation rose sharply, suggesting increased availability of moisture in this area. This is interpreted as a cooling effect due to the proximity to a large body of water to the study site and is attributed to the marine transgression into Baie des Chaleurs following the discharge of glacial lakes Agassiz and Barlow-Ojibway into the Great Lakes and Goldthwait Sea and the isostatic adjustment of the landmass. The cooling effect was recorded by a vegetation change from ca. 9450 to 8100 BP. Within that period, from ca. 8500 to ca. 8400 BP, the vegetation did not record the effect of the proximity to the sea. This period is postulated to be a period of low water levels in the Baie. Recovery to the regional climate norm occurred after 8100 BP when the climate was warmer than today. Since then the climate gradually cooled.